PEMODERASIAN LOCUS OF CONTROL DALAM PENGARUH AUDIT TENURE PADA KUALITAS AUDIT - Krisna, Adisti Maharani; Wirama, Dewa Gede; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
The purpose of this study is to obtain empirical evidence about the ability of locus of control in moderating the influence of audit tenure on audit quality by auditors at Public Accounting Firm (KAP) in the Province of Bali. This study was conducted in 2016. The main theory in this research is contigency theory and  supported by social learning theory and regulatory theory. The population in this study are all auditors at the Public Accounting Firm (KAP) in the Province of Bali, as many as 85 people. The sampling technique used is nonprobability sampling with saturated sampling method. The main reason for the selection samples method is because the population is relatively small. The instruments have been examined for its validity and reliability. The model also passed the classical assumption test. The analysis regression technique used is Moderated Regression Analysis (MRA). The results shows that locus of control moderates the effect of audit tenure on audit quality.
Keywords: Audit Quality, Audit Tenure, Locus of Control